Tradition, Wisdom and Negotiating Marriage and Inheritance Disputes on Javanese Muslim - Huda, Miftahul; Purnomo, Agus; Mun'im, Abdul; Aminuddin, Lutfi Hadi; Santoso, Lukman (Institut Agama Islam Negeri Curup, 2024)
This study aims to find a negotiation model in the tradition of Javanese Muslim communities in resolving disputes regarding marriage and inheritance restrictions. When the reality of resolving marriage and inheritance disputes impacts family and community strife, this becomes crucial. The qualitative paradigm was used to construct this research, which included a series of observations and in-depth interviews with the disputed families and focus group discussions with informants in the East Java community. This research discovers three models for resolving the tradition of avoiding marriage and inheritance disputes in Javanese Muslim society with social components in a heterogeneous society. 1) negotiating the traditional cum theology model, 2) negotiating the tradition and law model, and 3) negotiating the traditional wisdom model. Furthermore, when many cultural traditions fade, the growing negotiation model can serve as the foundation for policy for local governments in generating variants of the nation's culturalÂ traditions.